Renal-infiltrating CD11c+ cells are pathogenic in murine lupus nephritis through promoting CD4+ T cell responses. (18th August 2017) - Liao, X; Ren, J; Reihl, A; Pirapakaran, T; Sreekumar, B; Cecere, T E; Reilly, C M; Luo, X M
Summary: Lupus nephritis (LN) is a major manifestation of systemic lupus erythematosus (SLE), causing morbidity and mortality in 40–60% of SLE patients. The pathogenic mechanisms of LN are not completely understood. Recent studies have demonstrated the presence of various immune cell populations in lupus nephritic kidneys of both SLE patients and lupus-prone mice. These cells may play important pathogenic or regulatory roles in situ to promote or sustain LN. Here, using lupus-prone mouse models, we showed the pathogenic role of a kidney-infiltrating CD11c + myeloid cell population in LN. These CD11c + cells accumulated in the kidneys of lupus-prone mice as LN progressed. Surface markers of this population suggest their dendritic cell identity and differentiation from lymphocyte antigen 6 complex (Ly6C) low mature monocytes. The cytokine/chemokine profile of these renal-infiltrating CD11c + cells suggests their roles in promoting LN, which was confirmed further in a loss-of-function in-vivo study by using an antibody-drug conjugate (ADC) strategy targeting CX3 CR1, a chemokine receptor expressed highly on these CD11c + cells. However, CX3 CR1 was dispensable for the homing of CD11c + cells into lupus nephritic kidneys. Finally, we found that these CD11c + cells co-localized with infiltrating T cells in the kidney. Using an ex- vivo co-culture system, we showed that renal-infiltrating CD11c + cells promoted the survival, proliferation and interferon-γ production of renal-infiltrating CD4 + T cells, suggesting a T cell-dependent mechanism by which these CD11c + cells promote LN. Together, our results identify a pathogenic kidney-infiltrating CD11c + cell population promoting LN progression, which could be a new therapeutic target for the treatment of LN. Graphical Abstract: